(untitled) (Revista Brasileira de Plantas Medicinais, 2025)
Essential oils have been used as a natural alternative in the prevention and treatment of diseases that affect human health. The aim of this work was to determine the chemical composition and antibacterial activity of the essential oils of Lavandula angustifolia, Pogostemon cablin, Rosmarinus officinalis, Thymus vulgaris, Hedyosmun brasiliense, Psidium guajava, Baccharis dracunculifolia and Schinus terebinthifolius against bacteria Staphylococcus aureus, Salmonella enteritidis, Escherichia coli and Pseudomonas aeruginosa. The essential oils were analyzed by gas chromatography coupled to mass spectrometry. The antibacterial activity was determined by microdilution in broth, showing minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The chemical composition of the evaluated oils was based on monoterpenes and sesquiterpenes. The essential oil of Thymus vulgaris was highlighted with MIC of 0.195 and MBC of 1.56 µl/ml against S. aureus, 0.195 and 50 µl/ml for S. enteritidis; 0.390 µl/ml and 0.780 µl/ml for E. coli and 0.780 and 12.5 µl/ml against P. aeruginosa, respectively. The variability of specific components of the essential oils is very interesting and of economic importance, due to the therapeutic and aromatizing potential of these oils. The oils of L. angustifólia, T. vulgaris, R. officinalis, B. dracunculifolia, P. guajava and S. terebinthifolius showed activity in vitro against S. aureus, E. coli, S. enteritidis and stronger for P. aeruginosa. The oil of Thymus vulgaris presented the best results when its antibacterial activities were evaluated. The evaluated oils had an inhibitory effect on the microorganisms studied and the gram-positive bacteria were more sensitive to the effects of the essential oils when compared to the gram-negative bacteria. The essential oils evaluated in this study represent an important alternative for controlling bacterial infections.